Preparation and Characterization of Dual-Network Multifunctional Hydrogels Based on Peach Gum Polysaccharides: Ultrafast Self-Healing Ability, Favorable Mechanical Tunability, and Controlled Release Properties - Boyu Liu; Yumeng Han; Zhenqing Zhang; Jianing Hao; Hao Wan; Yongguo Jin; Qi Xu (Gels)
Natural hydrogels have attracted considerable attention due to advantages of moisturizing, biocompatibility, and plasticity. In this study, a dual-network oxidized peach gum polysaccharide–carboxymethyl chitosan (OPGC) hydrogels with ultrafast self-healing ability was constructed by self-assembly using oxidized peach gum polysaccharide (OPGP) and carboxymethyl chitosan (CMCS). After complete fracture, OPGC hydrogels rapidly self-healed within 30 s due to the dual-network structure formed by the hydrogen bonds between the OPGP molecules and the Schiff base bonds between them and the CMCS. Meanwhile, the hydrogels exhibited good injectability and biocompatibility. With the increase of CMCS from 0.5 wt% to 2.5 wt%, the gel formation time of OPGC hydrogels was drastically shortened from 12 min to 3 min, while the strength and water-holding capacity were enhanced. Furthermore, experimental in vitro and in vivo animal studies demonstrated excellent drug loading capacity of OPGC hydrogels, and the release rate of bactericide could be controlled by adjusting the content of CMCS. The OPGC hydrogels have outstanding properties for potential applications in the health and medical fields.